Factors Influencing Dividend Policy of Manufacturing Companies Listed on The Indonesia Stock Exchange - Kristiani, Renty; Matusin, Anita Roosmalina (Journal of Applied Business, Taxation and Economics Research, 2023)
The purpose of this study is to determine the factors that influence dividend policy in manufacturing companies listed on the Indonesian stock exchange. This research is a quantitative research with a research design in the form of hypotesis testing (hypothesis test). The analytical method in this study uses panel data regression analysis. Data were obtained from the financial reports of manufacturing companies that have been published and listed on the Indonesian Stock Exchange (IDX) for five consecutive years, from 2016 to 2020. The sample in this study was taken using a purposive sampling technique, namely 31 manufacturing companies. has been published and listed on the Indonesian Stock Exchange (IDX). The collected data was then tested using the Eviews 10.0 software. the research results show that there is no influence between financial leverage, managerial ownership, return on assets, firm size and investment opportunity on dividend policy. The advice that researchers can give for further research is that it is better to choose a company that distributes dividends successively so that differences and research updates can be generated